2016
DOI: 10.1001/jamaneurol.2016.1325
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Coenzyme Q10 Levels in Patients With Multiple System Atrophy

Abstract: IMPORTANCE Multiple system atrophy (MSA) is an intractable neurodegenerative disease characterized by autonomic failure in addition to various combinations of parkinsonism, cerebellar ataxia, and pyramidal dysfunction. It has recently been reported that functionally impaired variants of COQ2, which encodes an essential enzyme in the biosynthetic pathway of coenzyme Q10 (CoQ10), are associated with MSA. However, little is known about the role of CoQ10 in the pathogenesis of MSA. OBJECTIVE To compare the levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 17 publications
2
33
2
1
Order By: Relevance
“…However, based on pathological and molecular evidence from MSA human studies and animal models, several factors seem to be definitely associated with the disease and may serve as therapeutic targets for disease modification (Fig. 1), including the abnormal accumulation of α-syn [30][31][32][33]43,44], microglial activation and neuroinflammation [52,[54][55][56][57][58][59][60][61]89], autophagy disturbances [64][65][66][67], mitochondrial dysfunction [12,15,66,[68][69][70][71][72][73][74] and oxidative stress [76]. Yet the primary event which triggers the whole pathogenic cascade is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, based on pathological and molecular evidence from MSA human studies and animal models, several factors seem to be definitely associated with the disease and may serve as therapeutic targets for disease modification (Fig. 1), including the abnormal accumulation of α-syn [30][31][32][33]43,44], microglial activation and neuroinflammation [52,[54][55][56][57][58][59][60][61]89], autophagy disturbances [64][65][66][67], mitochondrial dysfunction [12,15,66,[68][69][70][71][72][73][74] and oxidative stress [76]. Yet the primary event which triggers the whole pathogenic cascade is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, MSA patients showed reduced levels of CoQ10 in cerebrospinal fluid, plasma/serum and cerebellum [68][69][70][71][72][73], which may lead to decreased electron transport in mitochondria and increased vulnerability to oxidative stress [68,69]. Recent studies with MSA fibroblast and iPSCs-derived dopaminergic neurons observed reduced CoQ10 levels and up-regulation of some CoQ10 biosynthesis enzymes in MSA patients compared to healthy controls [66,67,74].…”
Section: Other Translational Therapies For Msamentioning
confidence: 99%
See 1 more Smart Citation
“…After controlling for COQ2 genotypes, patients with MSA still had significantly lower levels of CoQ10, indicating that the lower plasma levels of CoQ10 in patients with MSA cannot be attributed to COQ2 mutations. 12 In addition, patients with the cerebellar and parkinsonism subtypes of MSA had similarly decreased plasma levels of CoQ10. Consistent with these observations, Kasai et al 13 found a decreased ratio of serum CoQ10 to cholesterol in patients with MSA.…”
mentioning
confidence: 99%
“…And, if so, might it serve as a biomarker for MSA? In this issue of JAMA Neurology , Mitsui and colleagues 12 have addressed these issues by investigating plasma levels of CoQ10 in 44 patients with MSA and 39 controls. They found a 30% reduction of plasma levels of CoQ10 in patients with MSA.…”
mentioning
confidence: 99%